Предмет: Математика,
автор: tovpaschkoly
9(x - 3) - 4(7 – 3x) - 3 = -8x.
Ответы
Автор ответа:
1
Ответ: 2
Пошаговое объяснение:
9(х-3)-4(7-3х)-3=-8х
9х-27-28+12х-3=-8х
9х+12х+8х=27+28+3
29х=58
х=58:29
х=2
Автор ответа:
1
Ответ: 2
Пошаговое объяснение:
На фото
Р. с : если можно, пометь этот ответ лучшим.
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: vita18052002
Предмет: Другие предметы,
автор: dashakriv1996
Предмет: Русский язык,
автор: Джульетта01092001
Предмет: Математика,
автор: Armansungatov
Предмет: Химия,
автор: vasilyramus